Hubungan Antara Perilaku Konsumen dengan Keputusan Pembelian Sayur dan Buah Secara Online di Kalangan Mahasiswa Universitas Padjadjaran - Nathanael, Caesar Radya; Budiman, Muhammad Arief (Universitas Galuh, 2025)
E-commerce in Indonesia has grown rapidly with the following increased use of the internet, which has also influenced the rise of online agricultural product transactions. This growth is driven by several benefits, such as saving on transportation costs, labour, and time. However, it is unfortunate that the consumption of vegetables and fruits in Indonesia remains relatively low. As a part of the Indonesian society, university students in Indonesia also exhibit low consumption levels of vegetables and fruits, which is influenced by the changes in their consumption behaviour since the start of college. Therefore, this study aims to investigate whether there is a relationship between consumer behaviour and online purchasing decisions for vegetables and fruits among university students. The respondents in this study were 100 undergraduate and diploma students from the Faculty of Agriculture at Universitas Padjadjaran. The analytical methods used in this research included descriptive statistics, inferential statistics using the chi-square test, and cross-tabulation analysis. The results of the study indicate that cultural factor, social factor, and personality factor are related to consumer purchase decisions. Cultural and personality factors were found to have a significant impact on students' decisions to purchase vegetables and fruits online. While social factors, although not significant, also influence consumers' decisions to purchase vegetables and fruits via online.